Development and Validation of UV-Spectrophotometric Method for Quantitative Assessment of Metronidazole in the «Metromed® Neo» Solution for Infusion - Khilola Ganieva1, Akhmad Yunuskhodjaev2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Metronidazole is widely used in medicine and issues of quality control of its dosage formsare relevant. Objective - development and validation of a UV spectrophotometric method for monitoring thequality of metronidazole in the «Metromed® Neo» solution for infusion.Materials and Method: The object of the study was a solution for infusion containing metronidazole. Themethod used is UV spectrophotometry.Results: The relative error of the developed UV spectrophotometric method for the quantitative assessmentof metronidazole in the solution for infusion was 1.9%. Validation characteristics of the method are withinacceptable limits.Conclusion: A UV spectrophotometric technique was developed and validated to assess the quality ofthe solution for infusion containing metronidazole. The results of the studies make it possible to use thedeveloped and validated methodology in assessing the quality of metronidazole.